Implementasi Teknologi Budidaya Ikan Patin Pustina (Pangasionodon hypophthalmus) Berbasis Probiotik dan Pakan Herbal pada Kelompok Budidaya Pokdakan Bangun Makmur, Desa Parit Aman, Kecamatan Bangko, Kabupaten Rokan Hilir - Rusliadi, Rusliadi; Masjudi, Heri; Putra, Iskandar; Sumiarsih, Eni; Firmansyah, Rodhi; Yulindra, Ade; Mutamima, Annisa; Yudha, Pajri Ananta (Unri Conference Series: Community Engagement, 2024)
The fish farming group "Bangun Makmur" from Parit Aman Village, Bangko District, Rokan Hilir Regency, has actively participated in a community service program aimed at introducing and implementing fish farming technologies, particularly probiotic technology for aquaculture water and feed technology enhanced with herbal additives (rabal and white turmeric). The program also seeks to increase income and create job opportunities in the area. The methods used include lectures, practical training, mentoring, as well as monitoring and evaluation of the fish farming process. Through discussion and practice, commonly referred to as "learning by doing," the majority of participants successfully grasped the concept of probiotic technology and herbal feed. Evaluation results indicated that some community members have started applying the technology by constructing ponds and conducting effective fish farming operations. This initiative marks a shift from dependence on the fluctuating palm oil sector to a sustainable alternative enterprise. The outcomes of this community service underscore the crucial role of technology and education in enhancing economic self-reliance and strengthening the local fisheries sector.